An updated checklist of the vascular flora of Sierra Nevada (SE Spain) - Lorite, Juan (Phytotaxa, 2016)
To have an updated checklist available for a given area is crucial for many purposes (educational, conservation, management, etc.). In this paper, a complete and updated checklist of the vascular flora of Sierra Nevada mountain range (SE Spain), a recognized hotspot for plant diversity in the Mediterranean basin, is presented. It includes 2,353 taxa, 359 more than in the previous checklist (an increase of 15.25%). Also, data are shown on composition (in terms of families, number of hybrids, native/alien species, endemics, etc.) and threat status according to the IUCN. The result is a complete and updated checklist flora of this recognised biodiversity Mediterranean hotspot.